Strategy of Dispute Resolution By Business Enterprises in Online Sale Transactions - Joris, Tesalonika Luana; Saija, Ronald; Pariela, Marcelo Valentino Geovani (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The practice of online buying and selling, there are often defaults that disadvantage related parties and cause disputes. Dispute resolution is often faced with problems such as complicated procedures, lack of public understanding of available mechanisms, imbalance of power between business owners and consumers, and limited capacity of dispute resolution institutions.Purposes of the Research: The purpose of this research is to find out how consumer protection against online buying and selling disputes.Methods of the Research: This research is normative in approach with a statutory approach and conceptual approach. The research sources are legal sources related to online transactions in order to increase understanding of the principles of justice, consumer protection, and dispute resolution due to default.Findings of the Research: The results show that as a settlement of disputes due to default, it is necessary to make preventive efforts, namely being aware of the rights and obligations as buyers and sellers to prevent default and repressive efforts for consumer protection with compensation and which can be resolved by litigation and non-litigation. Dispute resolution needs to be synchronized with existing regulations on each e-commerce platform, so that consumers and sellers can follow the dispute resolution mechanism effectively.